Moral Ekonomi Islam, Maqasid Syari’ah dan Kapitalisme - Ansharullah Ansharullah; Jalaluddin Jalaluddin; Zainal Abidin; Zaki Mubarak (Interdisciplinary Explorations in Research Journal, 2026)
This article examines the relationship between Islamic moral economy, maqasid al-shari'ah, and the practices of Islamic financial institutions within the context of modern capitalism. The study employs a library research method with a descriptive-critical approach to the literature on Islamic economics, maqasid al-shari'ah, and Islamic finance. The findings reveal that Islamic economics is fundamentally grounded in the principles of tawhid, justice, public welfare, and balance, aiming to establish a human-centered economic system. However, in practice, many Islamic financial institutions have increasingly converged with the capitalist financial system, prioritizing profitability over moral and social values. The dominance of debt-based financing, particularly murabahah, reflects a shift from the principle of risk sharing toward risk transfer, resulting in the incomplete realization of the substantive objectives of maqasid al-shari'ah. Furthermore, the classical framework of maqasid al-shari'ah requires reinterpretation to address contemporary economic challenges related to social justice, community empowerment, and environmental sustainability. This article argues for the reorientation of Islamic finance toward the principles of Islamic moral economy, emphasizing justice, partnership, and collective welfare as the primary objectives of Islamic financial institutions.